Is there a place for hair analysis in doping controls? - Rivier, L. (Forensic Science International, 2000)
The actual antidoping control rules applied in sports (as established by the International Olympic Committee and the International Sport Federations) state that a positive case is chemically established by the unequivocal detection of a forbidden parent molecule and/or any of its metabolite(s) in urine, no matter the amounts which were administered and when the drug was taken. Screening is accomplished most of the time by using GC-MS procedures. These have been optimized to detect most if not all of the forbidden compounds which are put on a list. Recently, attempts have been made on scalp hair to demonstrate the value of this matrix as a possible means for differentiating between therapeutic use and doping abuse. In particular, GC-mass selective detector and GC-high resolution MS were successfully applied to treated animals and body-builders for anabolic agents (steroids and beta-2-agonists) at high sensitivity detection (low ng/g level). Naturally occurring molecules, like testosterone and its metabolites, could also be differentiated from their synthetic counterparts. Positive cases are more often challenged in courts and retrospectivity in time of the drug(s) intake is becoming an important issue for evaluating the responsibility of the person. This is can be based on hair analyses if the drugs have been taken at regular intervals. Stimulants and narcotics are often used in sports like drug of abuse in the ordinary social contexts. On the other hand, anabolic agents, when taken to improve the physical performances, follow complex regimens with the mixing of various formulas and dosages. Scalp hair references ranges for these as well as for endogenous substances still wait to be established statistically for competing, well-trained athletes. The incorporation rate into blond or gray hair is poorer than that of dark colored hair raising the question of individuals equality against the controls, a very important matter of concern for the sport's governing bodies. The frequency of hair cutting and short hair cuts necessary to gain speed in specific sports like swimming are other critical factors. On the other hands, irregular hair growth, associated with the washout effect through multiple washing and staining processes over expanded time intervals can cause concentrating or diluting effects. So far, a minority of prohibited substances could be detected in scalp hair with the sensitivity and specificity required in the context of the sport's activities. From the above, clear limitations of the usefulness of hair analysis in doping control analysis are obvious until a lot more data relevant to this particular field have been collected.